Aqueous two-phase system for recovery of lignin peroxidase from Amauroderma Rugosum liquid mycelia medium / Linda Jong Wan Yng - Jong, Linda Wan Yng (2014)

(untitled)
Amauroderma rugosum is a wild mushroom spesies widely distributed in tropics and is classified under class Basidiomycetes. The class Basidiomycetes is well-known for their abilities of producing lignocellulolytic enzymes such as lignin peroxidase (LiP), laccase (Lac) and manganese peroxidase (MnP). The Amauroderma rugosum produce lignin peroxidase in the medium supplemented with potato dextrose broth (PDB), 0.5 % (w/v) of yeast, 1 % (w/v) of saw dust and 150 μM (w/v) of copper with shaking speed of 120 rpm and 14 days duration gave the lignin peroxidase (LiP) activity of 105.68 ±5.87 U/ml (w/v). The utilization of the agricultural by-products (rubber wood saw dust) successfully induced a higher production of lignin peroxidase (LiP). The aim of this study was the primary extraction and recovery of lignin peroxidase (LiP) from Amauroderma rugosum using the rapid and low cost aqueous two phase system. There were a total of 25 systems from five PEG molecular weights; PEG600; PEG 1000, PEG 1500, PEG 3350 and PEG 8000 being tested. The system two of PEG 600 consisted 15% (w/v) polyethylene glycol (PEG) and 16 % (w/v) phosphate salts and tie-lie line 34.10 showed an increase of the top phase lignin peroxidase (LiP) activity to 89.29±19.35 U/ml (w/v) from the crude enzyme activity of 85.37±2.22 U/ml (w/v) . This system also gave the highest top phase purification factor (PFT) of 1.33±0.62 with a yield of 72.18±8.50 % (w/v). In overall, the volume ratio of 0.62, pH 8.0 and 10 % (w/v) crude enzyme adding were able to produce the optimum result. The addition of salt to the system gave no significant difference to the purification factor. The optimized ATPs parameters gave the optimum top phase purification factor (PFT) and yield of 6.25±3.21 and 81.08±4.92% (w/v) respectively. Lastly, SDS-PAGE and native-PAGE analysis of the purified lignin peroxidase from ATPS showed three distinctive bands sizes which were apparently 38 kDa, 45-46 kDa and 66kDa. The lignin peroxidase with band size of 66 kDa was never being reported in mushroom species to-date and this induced more interest to further investigate on this enzyme. In overall, the ATPs system was proven to be a promising method for primary extraction and purification of enzyme.